Cumulative Energy Imbalance in the Pediatric Intensive Care Unit: Role of Targeted Indirect Calorimetry - Mehta, Nilesh M. (2009)
INTRODUCTION: Failure to accurately estimate energy requirements may result in underfeeding or overfeeding. In this study, a dedicated multidisciplinary nutrition team measured energy expenditure in critically ill children. METHODS: Steady-state indirect calorimetry was used to obtain measured resting energy expenditure, which was compared with equation-estimated energy expenditure and the total energy intake for each subject. The children’s metabolic status was examined in relation to standard clinical characteristics. RESULTS: Sixteen measurements were performed in 14 patients admitted to the multidisciplinary pediatric intensive care unit over a period of 12 months. Mean age of subjects in this cohort was 11.2 years (range 1.6 months to 32 years) and included 7 males and 7 postoperative patients. Altered metabolism was detected in 13 of 14 subjects and in 15 of 16 (94%) measurements. There was no correlation between the metabolic status of subjects and their clinical characteristics. Average daily energy balance was 200 kcal/d (range −518 to +859 kcal/d). Agreement between measured resting energy expenditure and equation-estimated energy expenditure was poor, with mean bias of 72.3 ± 446 kcal/d (limits of agreement −801.9 to +946.5 kcal/d). CONCLUSIONS: A disparity was observed between equation-estimated energy expenditure, measured resting energy expenditure, and total energy intake, with a high incidence of underfeeding or overfeeding. A wide range of metabolic alterations were recorded, which could not be accurately predicted using standard clinical characteristics. Targeted indirect calorimetry on high-risk patients selected by a dedicated nutrition team may prevent cumulative excesses and deficits in energy balance.